Legal Aspects of the Implementation of Customary Laws in Enforcment in the Raja Ampat Marine Conservation Area in Raja Ampat, Southwest Papua - Meity Mongdong; Vieta Imelda Cornelis; Sri Astutik; Noenik Soekorini (CV. Era Digital Nusantara, 2025)
Indonesia, as the world's largest archipelago, has enormous marine resource potential, but the main challenge it faces is weak law enforcement in maintaining ecosystem sustainability. Raja Ampat, known as the center of marine biodiversity in the world, faces serious threats in the form of illegal fishing, hunting of protected species, and excessive exploitation of resources. The urgency of this research lies in the gap between the proven effectiveness of customary law and the limited legitimacy of formal state law. The main question asked is to what extent customary law can serve as an instrument for enforcing marine conservation law within the framework of the national legal system. This study uses a normative legal method with a statute and conceptual approach. Primary legal materials consist of legislation, court decisions, and regional regulations, while secondary legal materials consist of academic literature and previous research results. Data collection techniques were carried out through literature studies with qualitative analysis using deductive logic. The results of the study show that customary law, particularly the practice of sasi in Raja Ampat, has proven effective in increasing coral cover, improving fish biomass, and reducing violations by up to 90%. However, this effectiveness has not yet gained strong formal legitimacy in the national legal system. Constitutional recognition of customary law is still normative and is not yet supported by clear operational regulations. The conclusion of this study emphasizes that the integration of customary law into the national legal system through a co-management model is a strategic step to strengthen marine conservation. The practical implication is the need for regulations that support the role of indigenous peoples in monitoring, while theoretically this study enriches the study of legal pluralism. Further studies are recommended to explore the long-term impact of integrating customary law on the welfare of coastal communities and the resilience of marine ecosystems.